Una escuela para la diversidad: eficacia y tensiones del modelo de educación flexible “tejiendo saberes “en la población adulta. - Domínguez Zambrano, Angee Alexandra (Universidad Antonio Nariño, 2022)
This research is developed in the field of adult education and the flexible model "Weaving knowledge" attached to the Ministry of National Education of Colombia, to mean that education aimed at young people, adults and the elderly starts from knowledge and learning previous, and from the life experiences of the people, according to capacities, interests and expectations, allowing the strengthening of basic and civic competences that strengthen the social fabric; The purpose of which is to provide guidance on the education of young people and adults and analyze the relevance of the contents offered by the Flexible Educational Models in Colombia for the adult population in vulnerable conditions.